Fractionation stream components of wood-based biorefinery: New agents in active or intelligent primary food packaging? - Ehman, Nanci Vanesa (2023)
Active and intelligent packaging production helps to improve the food value chain, granting reliability to consumers. According to these two premises, these packaging concepts were born. Sustainability and food protection criteria are two fundamental aspects that can be achieved with wood components.